The Influence of Brand Image and Social Media Instagram on Consumer Buying Interest - Rika Utari; Arifudin; Roza Yulida (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The increasingly rapid development of the business sector in the era of digitalization has an impact on increasingly tight business competition, especially in the city of Pekanbaru. This requires business actors to be able to compete and attract the attention of consumers to be interested in buying products so they are not left behind. One way that business actors can do to face the increasingly competitive competition is through the formation of a positive brand image and the utilization of social media Instagram as digital marketing which is expected to influence consumer buying interest. The aim of this study is to analyze the influence of brand image and social media Instagram on consumer buying interest. Simple random sampling was used as the sampling method of this research by taking data through questionnaires from 120 respondents. SEM (Structural Equation Model) in AMOS 26 was used to analyze the data. The analysis results show that brand image and social media Instagram significantly influenced consumer buying interest. In addition, it was also found that social media Instagram significantly influenced brand image.